Quality of seeds of native corn from the Altos de Jalisco region - Sandoval-Santiago, Zeltzin R.; Bautista-Ramírez, Edgardo; Zelaya-Molina, Lily X.; Chávez-Díaz, Ismael F.; Pichardo-González, Juan M.; Sánchez-Abarca, Carlos (Revista Mexicana de Ciencias Agrícolas, 2025)
The loss in physiological quality increases when the temperature and relative humidity in storage are high. Hypothetically, the physiological quality of the seeds of native corn preserved by producers is low. This work aimed to evaluate the physiological quality of native corn seeds collected in the Altos de Jalisco region, Mexico. In May 2022, 21 samples of native corn were collected in the Altos de Jalisco Region. The tests carried out were weight of 100 seeds, germination, analysis of physical integrity, and grain color. In the weight of 100 seeds, the collections belonging to the Elotes Occidentales breed were the highest. Ten of the 21 collections did not exceed 90% germination. None of the mean variables for physical integrity showed significant differences. There were two accessions with white and yellow grain colorations that differ from what has been reported in the literature.
Keywords: Elotes Occidentales; germination; grain color; physical integrity